GE_GERICHTE C/3045/2014 vom 12. November 2014 - GE Cour de justice (2014)
DROIT D'ÊTRE ENTENDU ; RETRAIT DU DROIT DE GARDE ; PLACEMENT D'ENFANTS ; RELATIONS PERSONNELLES | Cst.29; CC.310.al1; CC.273.al1